The limits of intelligent personal assistants. (19th March 2015) - DALE, ROBERT
Abstract In almost every science fiction movie you'll see people conversing with machines. Of course, the rise of intelligent personal assistants means you probably do this yourself already. This posting asks: what's the difference? Also, recent news on Facebook acquisitions, spoken language translation, and sentiment analysis.